2000
DOI: 10.1046/j.1464-410x.2000.00506.x
|View full text |Cite
|
Sign up to set email alerts
|

A 10‐year follow‐up after Kegel pelvic floor muscle exercises for genuine stress incontinence

Abstract: Objective To determine the outcome 10 years after an individual course of pelvic¯oor muscle (PFM) exercises for genuine stress incontinence. Patients and methods Postal questionnaires were sent to 52 women who had undergone PFM training 10 years earlier, and their medical ®les were reviewed. The main outcome measures were the patients' selfassessment of therapy outcome, the frequency of PFM exercises at home, and the demand for surgery after physiotherapy. Results Forty-®ve women (87%; mean age 61 years) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
49
2
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(64 citation statements)
references
References 15 publications
2
49
2
11
Order By: Relevance
“…13 The favourable response to PFM training indicates that the improvement persists for a long time as reported in a study that there is a 66% chance that the favourable results will persist for at least 10 years. 14 The increase in strength of PFM can be confirmed by vaginal and anal surface electromyograms and urethral and vaginal squeeze pressure measurements. 15 Behavioural treatment options concentrate on traditional physical therapy techniques of education, therapeutic exercise, and the use of physical modalities that aid in the restoration of muscle function.…”
Section: Discussionmentioning
confidence: 86%
“…13 The favourable response to PFM training indicates that the improvement persists for a long time as reported in a study that there is a 66% chance that the favourable results will persist for at least 10 years. 14 The increase in strength of PFM can be confirmed by vaginal and anal surface electromyograms and urethral and vaginal squeeze pressure measurements. 15 Behavioural treatment options concentrate on traditional physical therapy techniques of education, therapeutic exercise, and the use of physical modalities that aid in the restoration of muscle function.…”
Section: Discussionmentioning
confidence: 86%
“…The physical therapy treatment given to the participants from the present observational study is widely described in the literature 2,16 , and it is considered effective for urinary loss due to stress. However, to date, the persistence of its clinical benefits in the long-term is still unclear 18,19 . The age of the patients in this study ranged from 34 to 75 years.…”
Section: Discussionmentioning
confidence: 99%
“…Bo and Talseth 27 found that 5 years after the end of treatment 61% of the group considered themselves satisfied with their condition. Cammu et al 19 reported that out of the 45 women treated with strengthening of the pelvic floor, 77% would recommend the treatment to friends and family members.…”
mentioning
confidence: 99%
“…furthermore, women in assisted bf therapy achieve results which are almost double compared to self-conducted Kegel exercises (26). it should be noted that it is very important to perform the exercises correctly because the likelihood that positive results will last for the next 10 years is increased by 66% if Kegel exercises in the initial stage are successfully and positively evaluated (27).…”
Section: Discussionmentioning
confidence: 99%